Peningkatan Produktivitas Leucophyllum frutescens Melalui Metode Stek Greenhouse pada Hara Nursery - Lestari, Amanda Dwi; Wana, Hermawan (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyze the increase in productivity of Leucophyllum frutescens through the greenhouse cutting method and its impact on the financial performance of Hara Nursery. Hara Nursery faces problems in the sale of Leucophyllum frutescens plants, where market demand cannot be met optimally and the production process is inefficient. To address these issues, the greenhouse cutting method was applied as a solution to improve plant productivity. Based on the results of a one-sample Z test, this method showed an effectiveness increase with a success rate of 64%, 14% higher than the company’s standard of 50%. Additionally, financial analysis showed significant increases in the company’s revenue and profit after the business development. Revenue increased from IDR 144,000,000 to IDR 300,000,000, while profit rose from IDR 52,044,348 to IDR 126,932,395. Based on the R/C ratio analysis, this business is considered feasible and profitable with the R/C ratio increasing from 1.6 to 1.9 after the business development. ROI analysis shows an 18% improvement after additional investment. The results of this study suggest that Hara Nursery continue and expand the use of the greenhouse cutting method as an effective investment strategy to increase productivity and profitability sustainably.